Analyzing the Consumer Behavior and Implications of Sustainable Consumption Among Generation Z - Hidayat, Taufiq; Nashirah, Azizah Fatin; Pangestuti, Irene Rini Demi (Research Horizon, 2024)
This study aims to examine the influence of social responsibility (SR), environmental concern (EC), and the use of social media related to environmental issues (SM) on sustainability intention (SI) and sustainable consumption behavior (SBC) among Gen Z (born 1997-2012). Using a cross-sectional design, data from 383 respondents or students in Indonesia were analyzed using the Sobel test to examine mediation pathways. The results indicate that SR, EC, and SM significantly influence SI, which in turn enhances SBC. This research found that sustainability intention plays a strong mediating role between SR, EC, and SM on sustainable consumption behavior. These findings underscore the importance of enhancing social responsibility, environmental concern, and interaction with environmental content on social media to promote sustainable consumption behavior among Gen Z. The limitations of this study include the use of a limited sample and a cross-sectional design. The implications of these findings involve marketing strategies and policies that support sustainability. Future research is recommended to expand the sample, use a longitudinal design, and consider external factors to better understand the dynamics of sustainable consumption behavior.